Composite drainage net material and preparation method thereof
By combining fluoro-frost modified rubber and guanidine-based diopylate with traditional polyethylene materials, composite drainage mesh materials are prepared, which solves the problem of insufficient performance of existing drainage mesh materials under impact and corrosion, and achieves higher wear resistance, antibacterial and anti-corrosion properties.
Patent Information
- Application Number
- CN202411364813.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing drainage network materials are prone to fracture or wear under the impact of long-term water flow and silt, and are difficult to exist stably in corrosive media, and have insufficient antibacterial and hydrophobic properties.
Composite drainage mesh materials are prepared through high-temperature mixing and twin-screw extrusion processes by high-temperature mixing and twin-screw extrusion.
It improves the impact resistance, wear resistance, corrosion resistance, antibacterial properties and water-repellent and antifouling capabilities of the drainage network, extends its service life and is suitable for a variety of environments.
Smart Images

Figure CN119161652B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drainage net materials, and in particular to a composite drainage net material and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, the drainage system, as the core part of the city's lifeline project, the stability of the drainage system is directly related to the city's operational safety and the quality of life of residents, especially in key areas such as transportation infrastructure, landfills, tunnel projects, etc. The stability of the drainage system is particularly critical. The drainage net is a key component of the drainage system, and the performance of the drainage net material directly affects the stability of the drainage system.
[0003] At present, most drainage nets use plastic as the base material. It has good plasticity and is easy to be thermally bonded with other materials such as permeable geotextiles, and has excellent drainage effects. However, with the complexity of the drainage environment, ordinary drainage nets have insufficient wear resistance and impact resistance, and it is difficult to remain stable under the impact of long-term water flow and sediment. They are prone to breakage or wear, which affects the drainage efficiency and is easy to introduce sediment into the discharged water. At the same time, ordinary drainage nets have average corrosion resistance, hydrophobicity and antifouling ability, and antibacterial properties. It is difficult to exist stably in corrosive media for a long time. When used in a dark and humid environment, the hydrophobicity and antifouling ability are poor. Oil stains adhere to the drainage net and breed microorganisms to form a biofilm on the surface of the drainage net, affecting the drainage efficiency, accelerating the corrosion process of the drainage net, and seriously affecting the service life of the drainage net.
[0004] Therefore, in actual use, the patent with publication number CN112709214A discloses a composite three-rib filter enhanced drainage net and its preparation method, which uses high-density polyethylene, ethylene-vinyl acetate copolymer, metallocene polyethylene, polyethylene and anti-aging agent to mix and melt to form a modified high polymer material as the drainage net matrix material, and bonds a permeable non-woven geotextile layer and a waterproof geotextile layer to form a composite drainage net. This type of drainage net has excellent mechanical properties, can withstand high loads, and has good permeability and flow rate when the load is large. However, the corrosion resistance of this type of drainage net material is general, which limits its long-term use in environments containing corrosive media such as acids and alkalis. Summary of the invention
[0005] The purpose of the present invention is to provide a composite drainage net material and a preparation method thereof, which solves the following technical problems: (1) The wear resistance and impact resistance of ordinary drainage net materials need to be improved. They are prone to breakage or wear under the impact of long-term water flow and sediment, which affects their service life; (2) Ordinary drainage net materials are difficult to exist stably in corrosive media for a long time, and their antibacterial ability and hydrophobic properties need to be improved. When used in a humid and dark environment, microorganisms are easy to attach to the surface of the drainage net to form a biofilm, which affects the drainage efficiency and is also easy to accelerate the corrosion process of the drainage net.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A composite drainage net material comprises the following raw materials in parts by weight: 50-80 parts of high-density polyethylene, 30-40 parts of linear low-density polyethylene, 15-18 parts of maleic anhydride grafted high-density polyethylene, 10-15 parts of fluorofuran modified rubber, 6-10 parts of guanidine diopside, 2-6 parts of antioxidant, 2-5 parts of plasticizer and 1-3 parts of lubricant.
[0008] Furthermore, the antioxidant is any one of 2,6-di-tert-butyl-4-ethylphenol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, and 2,6-di-tert-butyl-p-cresol; the plasticizer is any one of diisononyl phthalate, dioctyl phthalate, epoxidized soybean oil, and castor oil; and the lubricant is any one of liquid paraffin, calcium stearate, zinc stearate, and polyethylene wax.
[0009] Furthermore, the preparation method of the fluorocarbon modified rubber comprises the following steps:
[0010] S1: natural rubber is placed in toluene, mixed thoroughly, 2-fluoroacrylic acid and benzoyl peroxide are added, the temperature is raised to react, and the solvent is removed by distillation under reduced pressure to obtain fluorine-modified rubber;
[0011] S2: placing the fluorine-modified rubber in N,N-dimethylformamide, mixing thoroughly, adding glycidyl furfural ether and a catalyst, performing reduced pressure distillation, and collecting the product to obtain the fluorine-modified rubber.
[0012] In this scheme, under the action of benzoyl peroxide, the double bonds in the natural rubber structure react with the olefin groups in the 2-fluoroacrylic acid structure to obtain fluorine-modified rubber, and then under the action of a catalyst, the carboxyl groups in the fluorine-modified rubber structure react with the epoxy groups in the glycidyl furfural structure to obtain fluorine-modified rubber. The fluorine-modified rubber has multiple hydroxyl groups in its structure, can interact with the matrix material, has excellent compatibility, and has good toughness. It can improve the impact resistance of the drainage net, so that it is not easy to break when a large amount of water flows in. At the same time, its structure also contains fluorine elements, which can enhance the hydrophobicity of the drainage net, prevent the attachment of bacteria and pollutants, effectively reduce the residence time of water in the drainage net, and improve drainage efficiency. The carbon-fluorine bond in the structure has low surface energy, which can effectively prevent the invasion of corrosive media, and has a synergistic effect with the furfural group in its structure that has good chemical stability and can stably exist in corrosive media, thereby jointly enhancing the corrosion resistance of the drainage net and effectively broadening the application field of the drainage net.
[0013] Furthermore, in step S1, the temperature of the temperature-raising reaction is 60-65° C., and the time is 5-6 hours.
[0014] Furthermore, in step S2, the catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium sulfate, and tetrabutylammonium hydroxide.
[0015] Furthermore, the preparation method of the guanidine diopside comprises the following steps:
[0016] SS1: Place diopside in acetone, ultrasonically disperse for 10-15 minutes, add chloromethyldichloromethylsilane, heat to reflux reaction, cool to room temperature, filter, wash, and vacuum dry to obtain chloromethyl diopside;
[0017] SS2: Place chloromethyl diopside in toluene, ultrasonically disperse for 15-20 minutes, add polyhexamethyleneguanidine hydrochloride, heat to 50-55°C, stir continuously at a rate of 200-250r / min for 3-5 hours, cool to room temperature, filter, wash, and vacuum dry to obtain guanidine diopside.
[0018] In this scheme, the hydroxyl groups on the surface of diopside interact with the silicon-chlorine bonds in the structure of chloromethyldichloromethylsilane to obtain chloromethyldiopside, and the active chlorine on the surface of chloromethyldiopside reacts with the amino group in the structure of polyhexamethyleneguanidine hydrochloride to obtain guanidine diopside. After the diopside is organically modified, it can be evenly dispersed in the drainage net matrix material, effectively preventing agglomeration and significantly enhancing the wear resistance of the drainage net material. Using chloromethyldichloromethylsilane as a bridging agent, not only organic silicon is introduced on the surface of diopside to further enhance the hydrophobicity of the drainage net matrix material, but also polyhexamethyleneguanidine hydrochloride can be coated on the surface of diopside to form a shell-core structure. Polyhexamethyleneguanidine hydrochloride has a guanidine group, and the polymer is positively charged as a whole, which can interfere with the cell wall and cell membrane structure of microorganisms, inhibit the division and growth of microorganisms, and has excellent killing and inhibitory effects on a variety of microorganisms. It has a broad-spectrum antibacterial effect, so that the prepared drainage net material has antibacterial ability, effectively prevents the attachment of microorganisms and the corrosion of the drainage net caused by physiological activities, and significantly extends the service life of the drainage net.
[0019] Furthermore, in step SS1, the heating reflux reaction time is 24-36h.
[0020] Furthermore, in step SS2, the molecular weight of the polyhexamethyleneguanidine hydrochloride is 1000-2000.
[0021] A method for preparing a composite drainage net material comprises the following preparation steps:
[0022] Step 1, high-density polyethylene, linear low-density polyethylene, maleic anhydride grafted high-density polyethylene, fluorofuran modified rubber, guanidine diopside, antioxidant, plasticizer, and lubricant are placed in a high-speed mixer, the speed is set to 200-300 r / min, the temperature is raised to 190-200° C. and fully mixed for 2-3 hours to obtain a mixture;
[0023] Step 2: Transfer the mixed material to a twin-screw extruder, melt-extrude and granulate to obtain a drainage net material.
[0024] Furthermore, in step 2, the screw speed of the twin-screw extruder is 300-500r / min, the temperature of zone 1 of the twin-screw extruder is 210-220°C, the temperature of zone 2 is 190-200°C, the temperature of zone 3 is 180-190°C, and the temperature of zone 4 is 170-180°C.
[0025] Beneficial effects of the present invention:
[0026] The present invention prepares fluorofuran-modified rubber and guanidine diopside and adds them to the preparation process of the drainage net material, so that the prepared drainage net material has excellent corrosion resistance, impact resistance, wear resistance, antibacterial performance and hydrophobic and antifouling ability, can meet the use requirements in various environments, and has a long service life.
[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0029] Figure 1 The present invention is a flow chart for preparing the drainage net material. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The preparation methods of the fluorofuran-modified rubber and guanidine diopside described in the following examples and comparative examples of the present invention are as follows:
[0032] 1. Preparation of fluorocarbon modified rubber
[0033] S1: 3 g of natural rubber was placed in 60 ml of toluene, and after thorough mixing, 2.6 g of 2-fluoroacrylic acid and 0.2 g of benzoyl peroxide were added, and the temperature was raised to 60°C for reaction for 5 h. After the solvent was removed by distillation under reduced pressure, a fluorine-modified rubber was obtained;
[0034] The carboxyl content in the fluorine-modified rubber structure was tested by acid-base titration. The specific method is as follows: take 1g of fluorine-modified rubber as a sample and place it in 60ml of acetone, add an excess of 0.1mol / L potassium hydroxide ethanol solution, add 1 drop of phenolphthalein indicator, mix thoroughly, and use 0.1mol / L hydrochloric acid standard solution for back titration. After the color of the solution disappears, continue stirring for 20min, and continue titrating until the color reappears until the color disappears completely. At the same time, do a blank experiment, record the volume of potassium hydroxide ethanol solution and hydrochloric acid standard solution consumed, and calculate with reference to the following formula: Carboxyl content in sample = 0.045×C(V-V0)×100% / M; where 0.045 is the molar mass of the carboxyl group, kg / mol; C is the concentration of the hydrochloric acid standard solution, mol l / L; V is the volume of hydrochloric acid standard solution consumed in the sample, ml; V0 is the volume of hydrochloric acid standard solution consumed in the blank experiment, ml; M is the sample mass, g; After calculation, the carboxyl content in the sample is 15.3%.
[0035] S2: 3.2 g of fluorine-modified rubber was placed in 70 ml of N,N-dimethylformamide, and after thorough mixing, 2.8 g of glycidyl furfuryl ether and 0.15 g of tetrabutylammonium bromide were added, and the mixture was distilled under reduced pressure to collect the product to obtain fluorine-modified rubber.
[0036] The carboxyl content in the fluorofuran modified rubber was tested by acid-base titration. The specific experimental method was the same as step S1. After calculation, the carboxyl content in the fluorofuran modified rubber was 3.1%. The loss was due to the ring-opening reaction between the carboxyl group in the fluorofuran modified rubber and the epoxy group in the glycidyl furfural ether structure.
[0037] 2. Preparation of guanidine diopside
[0038] SS1: 2.5 g of diopside was placed in 100 ml of acetone, and after ultrasonic dispersion for 10 min, 1.8 g of chloromethyldichloromethylsilane was added, and the mixture was heated under reflux for 24 h. After cooling to room temperature, the mixture was filtered, washed, and vacuum dried to obtain chloromethyl diopside.
[0039] SS2: Place 3 g of chloromethyl diopside in 120 ml of toluene, ultrasonically disperse for 15 min, add 2 g of polyhexamethylene guanidine hydrochloride, heat to 50 ° C, stir continuously at a rate of 200 r / min for 3 h, cool to room temperature, filter, wash, and vacuum dry to obtain guanidine diopside.
[0040] The nitrogen element of chloromethyl diopside and guanidine diopside was analyzed using a CHN-8000B element analyzer. The analysis results show that chloromethyl diopside contains almost no nitrogen; the nitrogen content in guanidine diopside is 14.6%. The appearance of nitrogen is due to the reaction between the active chlorine in the structure of chloromethyl diopside and the amino group in the structure of polyhexamethyleneguanidine hydrochloride.
[0041] Example 1
[0042] Preparation of drainage net materials
[0043] Step 1, 50 parts of high-density polyethylene, 30 parts of linear low-density polyethylene, 15 parts of maleic anhydride grafted high-density polyethylene, 10 parts of fluorofuran modified rubber, 6 parts of guanidine diopside, 2 parts of 2,6-di-tert-butyl-4-ethylphenol, 2 parts of diisononyl phthalate, and 1 part of liquid paraffin are placed in a high-speed mixer, the speed is set to 200 r / min, the temperature is raised to 190° C. and mixed thoroughly for 2 hours to obtain a mixture;
[0044] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 300r / min, the temperature of zone 1 to 210°C, the temperature of zone 2 to 190°C, the temperature of zone 3 to 180°C, the temperature of zone 4 to 170°C, melt extrude and granulate to obtain drainage net material.
[0045] Example 2
[0046] Preparation of drainage net materials
[0047] Step 1: Place 65 parts of high-density polyethylene, 35 parts of linear low-density polyethylene, 16 parts of maleic anhydride grafted high-density polyethylene, 12 parts of fluorofuran modified rubber, 8 parts of guanidine diopside, 4 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3 parts of dioctyl phthalate, and 2 parts of calcium stearate in a high-speed mixer, set the speed to 250 r / min, heat to 195° C. and mix thoroughly for 2.5 hours to obtain a mixture;
[0048] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 400r / min, the temperature of zone 1 to 215°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 185°C, the temperature of zone 4 to 175°C, melt extrude and granulate to obtain drainage net material.
[0049] Example 3
[0050] Preparation of drainage net materials
[0051] Step 1, 80 parts of high-density polyethylene, 40 parts of linear low-density polyethylene, 18 parts of maleic anhydride grafted high-density polyethylene, 15 parts of fluorofuran modified rubber, 10 parts of guanidine diopside, 6 parts of 2,6-di-tert-butyl-p-cresol, 5 parts of epoxy soybean oil, and 3 parts of zinc stearate are placed in a high-speed mixer, the speed is set to 300 r / min, the temperature is raised to 200° C. and mixed thoroughly for 3 hours to obtain a mixture;
[0052] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 500r / min, the temperature of zone 1 to 220°C, the temperature of zone 2 to 200°C, the temperature of zone 3 to 190°C, the temperature of zone 4 to 180°C, melt-extrude and granulate to obtain drainage net material.
[0053] Comparative Example 1
[0054] Preparation of drainage net materials
[0055] Step 1: Place 65 parts of high-density polyethylene, 35 parts of linear low-density polyethylene, 16 parts of maleic anhydride grafted high-density polyethylene, 12 parts of fluorofuran modified rubber, 4 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3 parts of dioctyl phthalate, and 2 parts of calcium stearate in a high-speed mixer, set the speed to 250 r / min, heat to 195° C. and mix thoroughly for 2.5 hours to obtain a mixture;
[0056] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 400r / min, the temperature of zone 1 to 215°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 185°C, the temperature of zone 4 to 175°C, melt extrude and granulate to obtain drainage net material.
[0057] Comparative Example 2
[0058] Preparation of drainage net materials
[0059] Step 1, 65 parts of high-density polyethylene, 35 parts of linear low-density polyethylene, 16 parts of maleic anhydride grafted high-density polyethylene, 8 parts of guanidine diopside, 4 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3 parts of dioctyl phthalate, and 2 parts of calcium stearate are placed in a high-speed mixer, the speed is set to 250 r / min, the temperature is raised to 195° C. and mixed thoroughly for 2.5 hours to obtain a mixture;
[0060] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 400r / min, the temperature of zone 1 to 215°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 185°C, the temperature of zone 4 to 175°C, melt extrude and granulate to obtain drainage net material.
[0061] Comparative Example 3
[0062] Preparation of drainage net materials
[0063] Step 1: Place 65 parts of high-density polyethylene, 35 parts of linear low-density polyethylene, 16 parts of maleic anhydride grafted high-density polyethylene, 4 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3 parts of dioctyl phthalate, and 2 parts of calcium stearate in a high-speed mixer, set the speed to 250 r / min, heat to 195° C. and mix thoroughly for 2.5 hours to obtain a mixture;
[0064] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 400r / min, the temperature of zone 1 to 215°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 185°C, the temperature of zone 4 to 175°C, melt extrude and granulate to obtain drainage net material.
[0065] Comparative Example 4
[0066] Preparation of drainage net materials
[0067] Step 1: Place 65 parts of high-density polyethylene, 35 parts of linear low-density polyethylene, 16 parts of maleic anhydride grafted high-density polyethylene, 12 parts of fluorine-modified rubber, 8 parts of guanidine diopside, 4 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3 parts of dioctyl phthalate, and 2 parts of calcium stearate in a high-speed mixer, set the speed to 250 r / min, heat to 195° C. and mix thoroughly for 2.5 hours to obtain a mixture;
[0068] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 400r / min, the temperature of zone 1 to 215°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 185°C, the temperature of zone 4 to 175°C, melt extrude and granulate to obtain drainage net material.
[0069] Comparative Example 5
[0070] Preparation of drainage net materials
[0071] Step 1, 65 parts of high-density polyethylene, 35 parts of linear low-density polyethylene, 16 parts of maleic anhydride grafted high-density polyethylene, 12 parts of natural rubber, 8 parts of guanidine diopside, 4 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3 parts of dioctyl phthalate, and 2 parts of calcium stearate are placed in a high-speed mixer, the speed is set to 250 r / min, the temperature is raised to 195° C. and mixed thoroughly for 2.5 hours to obtain a mixture;
[0072] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 400r / min, the temperature of zone 1 to 215°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 185°C, the temperature of zone 4 to 175°C, melt extrude and granulate to obtain drainage net material.
[0073] Comparative Example 6
[0074] Preparation of drainage net materials
[0075] Step 1, 65 parts of high-density polyethylene, 35 parts of linear low-density polyethylene, 16 parts of maleic anhydride grafted high-density polyethylene, 12 parts of fluorofuran modified rubber, 8 parts of diopside, 4 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3 parts of dioctyl phthalate, and 2 parts of calcium stearate are placed in a high-speed mixer, the speed is set to 250r / min, the temperature is raised to 195°C and mixed thoroughly for 2.5h to obtain a mixture;
[0076] Step 2: Transfer the mixture to a twin-screw extruder, set the screw speed to 400r / min, the temperature of zone 1 to 215°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 185°C, the temperature of zone 4 to 175°C, melt extrude and granulate to obtain drainage net material.
[0077] Performance Testing
[0078] The drainage net materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were made into samples that met the specifications using a universal sample making machine. The tensile strength of the samples, the samples immersed in a 30% by mass dilute hydrochloric acid solution for 120 hours, and the samples immersed in a 30% by mass sodium hydroxide solution for 120 hours were tested with reference to standard GB / T1040-2006. The corrosion rate was calculated according to the following formula: Corrosion rate = (tensile strength of sample - tensile strength after corrosion) × 100% / tensile strength of sample. The smaller the corrosion rate, the stronger the anti-corrosion ability. The impact strength of the samples was tested with reference to standard GB / T1043.1-2008. Test; refer to standard GB / T31402-2023 to test the antibacterial performance of the sample; use Taber abrasion tester to test the wear resistance of the sample, place two grinding wheels on the sample, set the grinding wheel moving speed to 30r / min to perform a wear test on the sample, record the initial mass of the sample and the mass of the sample after 20000r wear, and calculate the wear value with reference to the following formula: Wear value = initial mass of the sample - mass of the sample after wear. The smaller the wear value, the stronger the wear resistance of the sample; use JC2000D2G contact angle tester to test the water contact angle of the sample to determine the hydrophobic and antifouling ability of the sample; see the table below for specific test results:
[0079]
[0080] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent corrosion resistance, impact resistance, wear resistance, antibacterial performance, and hydrophobic antifouling ability, can meet the use requirements in various fields, and have a long service life. In the sample prepared in Comparative Example 1, fluorine furan modified rubber is directly added, but guanidine diopside is not added, and the wear resistance and antibacterial ability need to be improved. In the sample prepared in Comparative Example 2, guanidine diopside is directly added, and fluorine furan modified rubber is not added. The corrosion resistance, hydrophobic antifouling ability and impact strength are not as good as those in the embodiment. In the sample prepared in Comparative Example 3, neither fluorine furan modified rubber nor guanidine diopside is added, so the sample has poor corrosion resistance, impact resistance, wear resistance, and antifouling ability. The antibacterial performance and hydrophobic antifouling ability are at a poor level. In the sample prepared in Comparative Example 4, fluorine-modified rubber and guanidine diopside are directly added, and fluorine furan modified rubber is not added. The sample has good anti-corrosion ability but is not as good as the embodiment. In the sample prepared in Comparative Example 5, natural rubber and guanidine diopside are directly added, and the anti-corrosion ability is poor. In the sample prepared in Comparative Example 6, diopside and fluorine furan modified rubber are directly added. The corrosion resistance, impact resistance, wear resistance and antifouling performance of the sample are not as good as the embodiment. This is because the diopside has agglomeration phenomenon in the matrix material. The antibacterial performance is poor because the surface of the diopside is not coated with the antibacterial agent polyhexamethylene guanidine hydrochloride, and the bacteria cannot be killed and expelled.
[0081] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A composite drainage net material, characterized in that: The invention comprises the following raw materials in parts by weight: 50-80 parts of high-density polyethylene, 30-40 parts of linear low-density polyethylene, 15-18 parts of maleic anhydride grafted high-density polyethylene, 10-15 parts of fluorofuran modified rubber, 6-10 parts of guanidine diopside, 2-6 parts of antioxidant, 2-5 parts of plasticizer, and 1-3 parts of lubricant; The preparation method of the fluorocarbon modified rubber comprises the following steps: S1: natural rubber is placed in toluene, mixed thoroughly, 2-fluoroacrylic acid and benzoyl peroxide are added, the temperature is raised to react, and the solvent is removed by distillation under reduced pressure to obtain fluorine-modified rubber; S2: placing the fluorine-modified rubber in N,N-dimethylformamide, mixing thoroughly, adding glycidyl furfural ether and a catalyst, performing reduced pressure distillation, and collecting the product to obtain the fluorine-modified rubber; The preparation method of the guanidine diopside comprises the following steps: SS1: Place diopside in acetone, ultrasonically disperse for 10-15 minutes, add chloromethyldichloromethylsilane, heat to reflux reaction, cool to room temperature, filter, wash, and vacuum dry to obtain chloromethyl diopside; SS2: Place chloromethyl diopside in toluene, ultrasonically disperse for 15-20 minutes, add polyhexamethyleneguanidine hydrochloride, heat to 50-55°C, stir continuously at a rate of 200-250r / min for 3-5 hours, cool to room temperature, filter, wash, and vacuum dry to obtain guanidine diopside.
2. A composite drainage net material according to claim 1, characterized in that: The antioxidant is any one of 2,6-di-tert-butyl-4-ethylphenol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, and 2,6-di-tert-butyl-p-cresol; the plasticizer is any one of diisononyl phthalate, dioctyl phthalate, epoxidized soybean oil, and castor oil; and the lubricant is any one of liquid paraffin, calcium stearate, zinc stearate, and polyethylene wax.
3. A composite drainage net material according to claim 1, characterized in that: In step S1, the temperature of the temperature-raising reaction is 60-65° C. and the time is 5-6 hours.
4. A composite drainage net material according to claim 1, characterized in that: In step S2, the catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium sulfate, and tetrabutylammonium hydroxide.
5. The composite drainage net material according to claim 1, characterized in that: In step SS1, the heating reflux reaction time is 24-36h.
6. A composite drainage net material according to claim 1, characterized in that: In step SS2, the molecular weight of the polyhexamethyleneguanidine hydrochloride is 1000-2000.
7. A method for preparing the composite drainage net material according to claim 1, characterized in that: The method comprises the following preparation steps: Step 1, high-density polyethylene, linear low-density polyethylene, maleic anhydride grafted high-density polyethylene, fluorofuran modified rubber, guanidine diopside, antioxidant, plasticizer, and lubricant are placed in a high-speed mixer, the speed is set to 200-300 r / min, the temperature is raised to 190-200° C. and fully mixed for 2-3 hours to obtain a mixture; Step 2: Transfer the mixed material to a twin-screw extruder, melt-extrude and granulate to obtain a drainage net material.
8. The method for preparing a composite drainage net material according to claim 7, characterized in that: In step 2, the screw speed of the twin-screw extruder is 300-500r / min, the temperature of zone 1 of the twin-screw extruder is 210-220°C, the temperature of zone 2 is 190-200°C, the temperature of zone 3 is 180-190°C, and the temperature of zone 4 is 170-180°C.
Citation Information
Patent Citations
Composite three-rib filtering reinforced drainage net and preparation method thereof
CN112709214A
Fluorosilicone rubber nano composite alloy three-proof paint and production method thereof
CN101230224A
Functionalized / thermally reversible crosslinked epichlorohydrin rubber and preparation method thereof
CN107474235A